Edukasi Penerapan Sistem ATS Antara PLN dan PLTS di SMA Negeri 2 Kesuma Bangsa - Meliala, Selamat; Akmal, Syarifah; Amani, Yasir; Putri, Raihan; Muhammad Jalil, Saifuddin (Jurnal SOLMA, 2023)
Background: Background: Electricity sources originating from PLN often cause sudden power outages that we don't know about, so this is very dangerous for sensitive electronic devices such as computers. To provide knowledge of automatic switch technology for quick transfers in selecting one source that is on quickly so that there is no momentary power outage on the computer load. Method: SMA Negeri 2 Kesuma Bangsa, the number of participants was 30 students, providing direction or education to participants in the form of ATS technology and providing insight into the use and design of ATS technology. As well as providing questionnaires before and after education on ATS implementation and scoring scores regarding understanding of the technology. Results: The student community was very enthusiastic about participating in the event and they understood the implementation of ATS between PLN and PLTS. Conclusion: Rooftop solar panels are used to increase additional power by 8 pieces with a capacity of 200 WP per piece and in the computer laboratory at SMAN 2 Kesuma Bangsa they can be used because the flashing is very small so there will be no momentary shutdown which will cause data loss.